HOSPITAL MANAGEMENT OF PROTEIN ENERGY MALNUTRITION, SUDAN EXPERIENCE - Mohamed Ahmed, Hassan; M.Ahmed, Sawsan (Gezira Journal of Health Sciences, 2006)
Objectives: To describe the protocol of management of severe protein energy malnutrition (PEM) and the treatment outcome of inpatient children using Gezira Formula and to compare it with the similar WHO protocol for the same purpose. Methods: All children less than five years of age admitted to Academy Charity Teaching Hospital (ACTH) with protein energy malnutrition were included in dietary management using Gezira Formula. Initial management with half strength formula was initiated until signs of improvement occur and thereafter maintained in full strength formula until recovery. The constituents of the two formulae were compared to WHO formula F75 & F100 as well as the outcome of treatment. Results: The total number of children studied was 396, representing 6.1% of the total number of children admitted to ACTH during the study period. The peak range of age at presentation was 6-24 months. Seven percent of children had marasmic-kwashiorkor, 13% had kwashiorkor, 48% had marasmus and 32% were under weight. The outcome of treatment was 72.5% improved, 10.4% died and 17.2% escaped from the ward before criteria for discharge was fulfilled. The management outcome was comparable with international standards suggested by WHO. Conclusion:  Gezira Formula is comparable to WHO formula for inpatient treatment of PEM, it is simple, cheap, easily understood by hospital staff and ingredients are available.